Women Entrepreneurs and their Challenges: A Case Study of Lucknow (PUSA Journal of Hospitality and Applied Sciences, 2024)
Background: Eentrepreneurships helps women to become self-sufficient and economically independent, then it is the  best way to empower them. Increased entrepreneurship has the capability to empower females politically, socially, and  financially. The path of women’s empowerment has given them more power over resources. It is important not just for  personal growth but also for the nation’s overall development. Objective: There are two objectives of the study: to study  the elements responsible for women to run their business and to examine the challenges struggled by women entrepreneurs  in managing their business. Methodology: Quantitative research was done. The data was collected from Lucknow city  of Uttar Pradesh state. Convenience sampling was done and 200 respondents were reached for data collection and 195  responses were finalised. A structured questionnaire was made for research and was spread to respondents through  Google forms and by personal interview. Mean value and reliability test were used to analyse the data. Results: The  Cronbach’s static value was found 0.975 which is acceptable for the study. The weighted mean score it has been found that  aspire to be independent ranked 1st (weighted mean score 2.8). Women requires financial need to run the business ranked  2nd (weighted mean score 2.7). Confirmation of family and career security are two important pillar to boost confidence  in oneself ranked 3rd (weighted mean score 2.3). Women faced challenges for building infrastructure for their business  ranked 1st (weighted mean score 3.5). Budgetary restrictions was the major issue for women entrepreneurs ranked 2nd (weighted mean score 3.4). Low mobility was third largest issue for the entrepreneurs ranked 3rd (weighted mean score  3.3). Conclusion: The study concludes that if women focus on the challenges faced by them in running business, they can  overcome the issues. Proper training is always required of the concerned business and majorly help from Government and  NGO’s can change the status of the women.
Keywords: women; entrepreneurs; business; challenges; government